Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Wayground Terhadap Kemampuan Pemahaman Konsep Matematis Murid Sekolah Dasar - Nuraeni, Ukeu; Almujab, Saiful; Nurhadi, Moh (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
: Interpreting and representing data remains difficult for a number of elementary pupils because the task requires more than computation. This research examined a learning sequence in which Problem Based Learning (PBL) was supported by Wayground and assessed its contribution to mathematical conceptual understanding. A quantitative quasi-experiment employing a nonequivalent pretest-posttest control-group design was conducted with third-grade pupils of SD Negeri 033 Asmi Bandung. From a population of 134 pupils, class III A and class III B were selected purposively as the experimental and comparison groups; each group contained 28 pupils. Evidence was gathered through essay-based tests, classroom observations, interviews, and documentation, and was processed with IBM SPSS Statistics 29.0. Observation scores for teacher and pupil participation were 87% and 86% in the experimental group, while the comparison group reached 82% and 77%. The experimental group recorded a mean N-Gain of 0.6489, compared with 0.5025 in the comparison group. An independent-samples t-test returned a two-tailed probability of 0.010, which was below 0.05. The findings indicate that integrating Wayground into the PBL sequence contributed significantly to pupils' mathematical conceptual understanding.